[OP.2A.08] HYPERTENSION AND CARDIOVASCULAR DISEASE IN GREECE: INTERIM ANALYSIS OF THE EMENO NATIONAL EPIDEMIOLOGICAL STUDY. (September 2016) - Stergiou, G.S.; Margetaki, A.; Boubouchairopoulou, N.; Mastrokostas, A.; Vantarakis, A.; Chlouverakis, G.; Rachiotis, G.; Trypsianis, G.; Voulgari, P.; Alamanos, I.; Karakosta, A.; Touloumi, G.
Abstract : Objective: To date no nationwide epidemiological study of cardiovascular disease has been performed in the general population in Greece. This study evaluated the prevalence of coronary heart disease and stroke in individuals with hypertension in a randomly selected general population sample of adults in Greece. Design and method: The EMENO survey (National Morbidity and Risk Factors Survey) supported by the European Social Fund and national funds, is currently performed in Greece, aiming to include 6, 000 adults aged > = 18 years. It is conducted using a multi-stage stratified random sampling method, involving localities throughout the country. Interviewers and physicians made home visits, where medical history, blood sample, and automated blood pressure (BP) measurements were taken (Microlife BPA100 Plus). An interim analysis of participants recruited from 03/2014 to 12/2015 was performed. Hypertension was defined as BP > 140/90 mmHg (systolic and/or diastolic) or diagnosed hypertension under treatment. The prevalence was evaluated with statistical methodology taking into account the design and additional adjustments for age and sex. Results: Overall 1, 503 subjects were considered as being hypertensives. Among them 8% had a history of coronary heart disease (CHD) (myocardial infarction, coronary artery bypass graft or angioplasty) (2% among normotensives, p < 0.001). 3% of hypertensives had a history of a stroke (permanent or transient) (1.3% among normotensives, p < 0.001). CHD was more common in normotensive men than in women (3.3% and 1.3% respectively, p < 0.01), with no such difference among hypertensives (9.5% and 7% accordingly, p = NS). There was no difference in the incidence of stroke in men and women, among both hypertensives and normotensives. Among CHD patients, 69% were hypertensives and 50% had uncontrolled hypertension (36% and 29% among individuals without CHD, p < 0.001). Among stroke patients, 58% had hypertension and 44.5% uncontrolled hypertension (37% and 30% among those without stroke, p = 0.02). Conclusions: In the general adult population in Greece, the prevalence of cardiovascular disease is 3–4 fold more common in hypertensives compared to normotensive, and is largely driven by CHD. About 50% of patients with cardiovascular disease have uncontrolled hypertension. A national interventional program for primary and secondary cardiovascular disease prevention is necessary.